Ischaemia-reperfusion-induced renal injury : pathogenesis & modulation implications for transplantation - Stokes, Karen (Trinity College (Dublin, Ireland). Department of Physiology, 2004)
Ischaemia-reperfusion is unavoidable during transplantation, but may promote allograft rejection. Preconditioning with a sub-lethal stress protects cells against a subsequent otherwise lethal stress, possibly through the induction of heat shock proteins. This thesis establishes a rat model of renal ischaemia-reperfusion injury and assesses the protective capability of several preconditioning methods. The most effective method was used to evaluate antigen expression and long-term protection.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin